Storyworlds: the hare and the tortoise - Akass, Susan (Heinemann UK, 2009)
*The Hare and the Tortoise* is a classic fable where a fast and overconfident hare challenges a slow-moving tortoise to a race. Despite the hare$1 (Bs speed, the tortoise wins by staying steady and persistent, teaching the lesson that "slow and steady wins the race."s